PERGESERAN IDENTITAS MAHASISWA: KORELASI RELIGIUSITAS DAN PERILAKU MAHASISWA IAIN MATARAM - Muslim, Sri Banun; Nashuddin, Nashuddin; Tahir, Masnun (LP2M IAIN Mataram, 2014)
Academic, social and intellectual identities attached to Students have not been substantially understood. As such are recognized when such identities are related to students morality in which their morality are viz a viz to modern life which full of rationalism and pragmatism. This research is carried out to understand such tendency and this research is conducted through applying field research with qualitative approach. The result shows that first, in students labile psyche condition, void of values, unstable identity, and lack of experiences upon the meaning of life, religion can be functioned as the protector which gives coolness and quietness in students lives. Second, student identity as an intellectual critic has been vanished due to their incapability to understand their own function and role in the society. Third, students in now time forget their own existence and they have experienced goal disorientation especially to the aim of their university education. Therefore in this context the significance of studentsâ identity reorientation is important.